A randomized waitlist‐controlled trial of cognitive behavior therapy to improve emotion regulation in children with autism. (23rd April 2018) - Weiss, Jonathan A.; Thomson, Kendra; Burnham Riosa, Priscilla; Albaum, Carly; Chan, Victoria; Maughan, Andrea; Tablon, Paula; Black, Karen
Abstract : Background: Mental health problems are common among individuals with autism spectrum disorder (ASD), and difficulties with emotion regulation processes may underlie these issues. Cognitive behavior therapy (CBT) is considered an efficacious treatment for anxiety in children with ASD. Additional research is needed to examine the efficacy of a transdiagnostic treatment approach, whereby the same treatment can be applied to multiple emotional problems, beyond solely anxiety. The purpose of the present study was to examine the efficacy of a manualized and individually delivered 10‐session, transdiagnostic CBT intervention, aimed at improving emotion regulation and mental health difficulties in children with ASD. Methods: Sixty‐eight children ( M age = 9.75, SD  = 1.27) and their parents participated in the study, randomly allocated to either a treatment immediate ( n  =   35) or waitlist control condition ( n  =   33) (ISRCTN #67079741). Parent‐, child‐, and clinician‐reported measures of emotion regulation and mental health were administered at baseline, postintervention/postwaitlist, and at 10‐week follow‐up. Results: Children in the treatment immediate condition demonstrated significant improvements on measures of emotion regulation (i.e., emotionality, emotion regulation abilities with social skills) and aspects of psychopathology (i.e., a composite measure of internalizing and externalizing symptoms, adaptive behaviors) compared to those in the waitlist control condition. Treatment gains were maintained at follow‐up. Conclusions: This study is the first transdiagnostic CBT efficacy trial for children with ASD. Additional investigations are needed to further establish its relative efficacy compared to more traditional models of CBT for children with ASD and other neurodevelopmental conditions.